2011
DOI: 10.4238/vol10-1gmr960
|View full text |Cite
|
Sign up to set email alerts
|

Allelic polymorphism, gene duplication and balancing selection of the MHC class II DAB gene of Cynoglossus semilaevis (Cynoglossidae)

Abstract: ABSTRACT. Major histocompatibility complex (MHC) genes play an important role in the immune response of vertebrates. Allelic polymorphism and evolutionary mechanism of MHC genes have been investigated in many mammals, but much less is known in teleosts. We examined the polymorphism, gene duplication and balancing selection of the MHC class II DAB gene of the half-smooth tongue sole (Cynoglossus semilaevis); 23 alleles were found in this species. Gene duplication manifested as three to six distinct sequences at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…Loci under positive selection, however, can be essential in distinguishing between recently diverged species and populations that are otherwise difficult to distinguish using neutral makers [14], [38]. Characterizing genomic regions under balancing selection could identify advantageous genes and alleles that move between populations, such as loci involved in disease resistance (e.g., [39]). Thus, a necessary first step in any genetic study is to accurately characterize suites of loci that match study objectives and ensure the application of appropriate analytical models and correct interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Loci under positive selection, however, can be essential in distinguishing between recently diverged species and populations that are otherwise difficult to distinguish using neutral makers [14], [38]. Characterizing genomic regions under balancing selection could identify advantageous genes and alleles that move between populations, such as loci involved in disease resistance (e.g., [39]). Thus, a necessary first step in any genetic study is to accurately characterize suites of loci that match study objectives and ensure the application of appropriate analytical models and correct interpretation of results.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism derives from the creek word πολυμορφία ” (polymorphia) and means “many or complex shapes”. The polymorphism found in the MHC class II genes is generally limited to exon 2, which encodes the peptide-binding groove [59]. Due to the high frequency of MHC alleles, most individuals will be heterozygous for each different MHC gene locus.…”
Section: The Major Histocompatibility Complex (Mhc)mentioning
confidence: 99%
“…Numerous studies have found multiple DAB loci in other fish species (Kruiswijk, Hermsen, Fujiki, Dixon, Savelkoul & Stet ; Li, Jiang, Han, Su, Yang & He ; Xu, Sun & Wang ). In this study, we found that individuals possessed, at most, four alleles.…”
Section: Discussionmentioning
confidence: 99%